Glossary of mental disorders and guide to their classification : for use in conjunction with the International Classification of Diseases, 8th revision. - World Health Organization (Geneva : World Health Organization, 1974)
Overzicht van de geestesziekten.
Includes index.
Keywords: Mental illness -- Classification; Psychology, Pathological -- Dictionaries